Relationships among knowledge-oriented leadership, customer knowledge management, innovation quality and firm performance in SMEs - Pornthip Chaithanapat; Prattana Punnakitikashem; Nay Chi Khin Khin Oo; Sirisuhk Rakthin (Journal of Innovation & Knowledge (JIK), 2022)
Drawing upon the literature on knowledge management, leadership, and innovation, this study investigates the possible associations among customer knowledge management, knowledge-oriented leadership, innovation quality, and firm performance in 283 small and medium-sized enterprises (SMEs) in Thailand. The mediating roles of customer knowledge management and knowledge-oriented leadership among these relationships are highlighted in the SMEs, wherein human resources and invested capital are limited. Therefore, the findings contribute to the extant literature by providing empirical evidence to support that customer knowledge management mediates in the relationship between knowledge-oriented leadership and innovation quality. In addition, innovation quality mediates the relationship between customer knowledge management and firm performance. Furthermore, the result supports the moderating effect of competitive intensity on the relationship between customer knowledge management and innovation quality. Finally, the theoretical implications for academics and managerial implications for SMEs' managers are discussed.
Keywords: C30; D83; L20; M10; M31; O30; 650; Customer knowledge management; Decent growth and economic work; Firm performance; Innovation quality; Knowledge-oriented leadership; SMEs